Factors associated with increased intra-abdominal pressure in patients undergoing cardiac surgery - AYKAÇ, ZEYNEP ZUHAL (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2020)
Background: The aim of this study was to investigate the intra-abdominal pressure changes and risk factors associated with increased intra-abdominal pressure in patients undergoing cardiac surgery. Methods: Between July 2016 and January 2017, a total of 100 patients (74 males, 26 females; mean age 55.9 +/- 14.3 years; range, 19 to 75 years) who underwent cardiac surgery under cardiopulmonary bypass were included in the study. Patients' data including demographic and clinical characteristics and intra- and postoperative data were recorded. Intra-abdominal pressure was measured via a urinary catheter after anesthesia induction, on admission to the intensive care unit, and at postoperative 12 and 24 h. The patients were divided into two groups according to the intra-abdominal pressure as Group 1 (>==12 mmHg; n=49) and Group 2 (<12 mmHg; n=51). Results: In the univariate regression analysis, high intra-abdominal pressure was related to intra-abdominal pressure measured after anesthesia induction (Odds Ratio = 0.70, p=0.001), age (odds ratio=0.95, p=0.004), hypertension (odds ratio=4.51, p=0.0001), duration of cardiopulmonary bypass (odds ratio=0.97, p=0.0001), intraoperative lactate levels (odds ratio=0.53, p=0.0001), use of red blood cells (odds ratio=0.24, p=0.0001), use of dopamine (odds ratio=0.21, p=0.002), dobutamine (odds ratio= 0.28, p=0.005), use of noradrenaline (odds ratio=0.25, p=0.016), postoperative lactate levels (odds ratio=0.60, p=0.0001), duration of cross-clamp (odds ratio=0.97, p=0.0001), atrial fibrillation (odds ratio=5.89, p=0.004), and acute kidney injury (odds ratio=8.33, p=0.048). In the multivariate analysis, the intra-abdominal pressure at baseline (odds ratio=0.70, p=0.045), age (odds ratio=0.93, p=0.032), hypertension (odds ratio=6.87, p=0.023), duration of cardiopulmonary bypass (odds ratio=0.98, p=0.062), intraoperative lactate levels (odds ratio=0.57, p=0.035), and use of red blood cells (odds ratio=0.19, p=0.003) remained statistically significant. Conclusion: Our study results suggest that age, hypertension, duration of cardiopulmonary bypass, intraoperative lactate levels, and use of red blood cells are risk factors associated with elevated intra- abdominal pressure in patients undergoing cardiac surgery. Increased awareness of these risk factors and the addition of intra-abdominal pressure measurement to the standard follow-up scheme in patients with variable hemodynamics, low cardiac output, and high lactate levels in the intensive care unit may be useful in early diagnosis of complications and in decreasing morbidity.
Keywords: Cardiac surgery; cardiopulmonary bypass; intra-abdominal pressure; risk factor; ABDOMINAL COMPARTMENT SYNDROME; PERFUSION-PRESSURE; HYPERTENSION; BYPASS